2002
DOI: 10.1038/sj.hdy.6800157
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in a narrow endemic snapdragon (Antirrhinum subbaeticum, Scrophulariaceae) using RAPD markers

Abstract: Antirrhinum subbaeticum is an endangered species inhabiting fragmented limestone cliffs. In the last 3 years, a drastic population decline has been observed in three of four known populations and the estimated number of surviving individuals is now close to 400. A RAPD study was conducted to evaluate the levels of genetic variation present in this species to improve conservation guidelines. Thity-nine polymorphic products identified 66.1% of the samples by unique RAPD multilocus profiles. A cluster analysis gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
5
15
1
3
Order By: Relevance
“…In other species, reduced variability after fragmentation has been found in small populations of Eucalyptus albens (Prober and Brown, 1994), as well as to some extent in Carapa guianensis (Dayanandan et al, 1999) and Swietenia humilis (White, Boshier and Powell, 1999). Also non-significant fragmentation effects on variability are reported, e.g., for Sorbus aucuparia (Bacles, Lowe and Ennos, 2004), Antirrhinum subbaeticum (Jime´nez et al, 2002) and for Silene nutans (van Rossum et al, 1997). The consequences of fragmentation may also be just the opposite of expectations: Fore´et al (1992) reported lower differentiation after fragmentation among stands of Acer saccharum.…”
Section: Discussionmentioning
confidence: 89%
“…In other species, reduced variability after fragmentation has been found in small populations of Eucalyptus albens (Prober and Brown, 1994), as well as to some extent in Carapa guianensis (Dayanandan et al, 1999) and Swietenia humilis (White, Boshier and Powell, 1999). Also non-significant fragmentation effects on variability are reported, e.g., for Sorbus aucuparia (Bacles, Lowe and Ennos, 2004), Antirrhinum subbaeticum (Jime´nez et al, 2002) and for Silene nutans (van Rossum et al, 1997). The consequences of fragmentation may also be just the opposite of expectations: Fore´et al (1992) reported lower differentiation after fragmentation among stands of Acer saccharum.…”
Section: Discussionmentioning
confidence: 89%
“…Within the Antirrhineae, Antirrhinum subbaeticum Gü emes, Sá nchez-Gó mez & Mateu., a self-compatible, rupicolous narrow-endemic form South-eastern Spain is closely related to A. valentinum Cav., with which it shares morphological and life history traits but the breeding system type (Mateu-André s and Segarra-Moragues 2004). A change in the type of breeding system towards selfing in A. subbaeticum likely produced the lowest levels of within-population genetic diversity of the genus and high levels of population differentiation in this species (Jimé nez et al 2002;Mateu-André s 2004) compared to both, moderate levels of genetic diversity within populations and population differentiation in A. valentinum (Mateu-André s and Segarra-Moragues 2000). A similar pattern was recovered from New World toadflaxes (Nuttalanthus Sutton) in which low levels of within-population genetic variation and high population divergence, with values falling in the range of the self-compatible taxa studied here, were related to self-compatibility and habitual autogamy (Crawford and Elisens 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Most widely distributed species of vascular plants have a high amount of withinpopulation genetic diversity (Barrett and Kohn, 1991;Hamrick and Godt, 1989). In particular, outbreeding, wind-pollinated and long-lived species tend to have higher levels of within-population genetic diversity than self-pollinated, annual or short-lived ones (Gabrielsen et al, 1997;Jime´nez et al, 2002;Martı´n et al, 1997;Scho¨nswetter et al, 2006;Segarra-Moragues and Catala´n, 2003). Low levels of genetic variability are commonly but not universally (Martı´n et al, 1997) found in rare or geographically restricted species.…”
Section: Introductionmentioning
confidence: 96%